Preface - Carlos Castillo-Chavez; Gerardo Chowell (Mathematical Biosciences and Engineering)
A new A/H1N1 influenza virus strain was officially reported/identified in Mexico City on April 13 2009 and over a period of two-weeks the WHO pandemic alert was moved from level 3 to level 5. By May 2, a total of 141 cases had been confirmed in 19 states across the USA. Additional cases were soon confirmed in fifteen countries in Europe, Canada, New Zealand, and Asia. The global reach of this novel strain became evident when a summer influenza incidence high was reached in Japan by May 16, 2009 [2, 4] just about a month after its identification in the New World.For more information please click the “Full Text” above.